Trip Attraction Model of Land Use for Industrial Area - Imma Widyawati Agustin; Budi Sugiarto Waloeya (Institut Teknologi Sepuluh Nopember, 2017)
Malang was a great city that has a diverse industry characteristics and there are spreadly in every district. The goals of industrial vehicles movement is shipping and distribution. There are some problems related to the road’s level of service, especially several points of delay and congestion due to the industrial vehicles movement and the limited capacity of the roads. The main purpose of the research is to create the trip attraction model of land use for industrial area as a basis to determine the effect of industrial vehicles movement on the road’s level of service in industrial area. The research used industrial distribution mapping, the road’s level of service analysis to determine the traffic condition, correlation analysis to determine the influence variables used and multiple linear regression analysis to identify the trip attraction model of land use. The Results showed that the most affected variables of the industrial vehicles movement are the number of employees (X3) and the delivery frequency (X6). The trip attraction model is Yindustry = 5.104 + 0.736 (X3) + 1.832 (X6) with 94.1 per cent of R square. The road’s level of service in Sunandar Priyo Sudarmo Road is C.